Engineering Design of a Transparent Modular Fermentor System Based on Local Microbiome Fermentation for Innovative Virgin Coconut Oil Production in Small and Medium Enterprises - Adriyan Warokka; Nodi Sompie; Herotje Siwi; Estrela Muaja; Jerry Purnama (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2026)
Natural fermentation offers an economical approach to Virgin Coconut Oil (VCO) production for tropical small and medium enterprises (SMEs). However, practitioners in North Sulawesi, Indonesia, face product inconsistency because they lack hygienic, purpose-built equipment. This study presents the engineering design of a 50-liter transparent modular fermentor constructed from food-grade acrylic (PMMA), featuring a DC 12V low-shear agitator and a single-unit decanter. Mechanical analyses—evaluating hydrostatic wall stress, vertical compressive loading, and torsional stress—demonstrated high factors of safety exceeding ASTM D4802-16 thresholds. The knock-down modular design, GMP-aligned surfaces, and full optical transparency enable real-time stratification monitoring. Designed with low energy consumption (<2 Wh per batch) suitable for off-grid solar power, this validated blueprint provides a scalable, replicable production technology for coconut-processing SMEs. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 8: Decent Work & Economic GrowthSDG 9: Industry, Innovation & InfrastructureSDG 12: Responsible Consumption & Production